Psychosocial health of patients receiving orthopaedic treatment in northern Tanzania: A cross-sectional study. (February 2020) - Obayemi, Joy E.; Card, Elizabeth B.; Shirima, Octavian; Massawe, Honest; Mandari, Faiton; Pallangyo, Anthony; Temu, Rogers; Premkumar, Ajay; Sheth, Neil P.
Abstract: Background: Patients with musculoskeletal injuries in Sub-Saharan Africa often receive prolonged inpatient treatment due to limited access to surgical care. Little is known regarding the psychosocial impact of prolonged conservative treatment for orthopaedic injuries, which may add to disability and preclude rehabilitation. Methods: A cross-sectional, questionnaire study was conducted to characterize the psychosocial health of orthopaedic inpatients at a tertiary hospital in Moshi, Tanzania. Three validated surveys assessing coping strategies, functional social support, and symptoms of depression were orally administered to all orthopaedic patients with a length of stay (LOS) ≥ 6 days by a Tanzanian orthopaedic specialist. Results: Fifty-nine patient surveys were completed, and revealed 92% (54) of patients were more likely to utilize more adaptive than maladaptive coping strategies. Patients with chest or spinal column injuries were more likely to use maladaptive coping strategies (p = 0·027). Patients with head injuries had more social support compared to others (p = 0·009). Lack of insurance, limited education, and rural origins were associated with less functional social support, although this finding did not reach statistical significance. 23·7% (14) of patients had symptoms consistent with mild depression, 33·9% (20) with moderate depression, and 3·4% (2) with moderately-severe depression. LOS was the only significant predictor for depression severity. Conclusions: 61% (36) of orthopaedic inpatients exhibited depressive symptoms, indicating that the psychosocial health in this population is sub-optimal. Mental health is a crucial element of successful orthopaedic care. Access to timely surgical care would greatly decrease LOS, the most prominent predictor of depressive symptom severity. Highlights: The majority of orthopaedic patients were found to have symptoms of depression. Length of stay was the only significant predictor of depression symptom severity. Patients with torso injuries tended to use more maladaptive coping strategies.